2018
DOI: 10.1177/0961203318793206
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells for lupus nephritis: a concise review of current knowledge

Abstract: Lupus nephritis (LN), a common manifestation of systemic lupus erythematosus (SLE), accounts for significant morbidity and mortality in SLE patients. Since the available standard therapies and biologic agents for LN are yet to achieve the desired response and have considerable secondary effects, stem cell therapy has now emerged as a new approach. This therapy involves the transplantation of hematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs). Our current review will highlight the progress of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 127 publications
0
11
0
1
Order By: Relevance
“…When the clinical condition is serious, high-dose immunoglobulin, plasma exchange, or haematopoietic stem cell or mesenchymal stem cell transplantation can be selected. However, the long-term use of corticosteroids or immunosuppressants may lead to serious infection and secondary malignant tumours, and the use of biological agents is also limited to a certain extent because of its high cost [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the clinical condition is serious, high-dose immunoglobulin, plasma exchange, or haematopoietic stem cell or mesenchymal stem cell transplantation can be selected. However, the long-term use of corticosteroids or immunosuppressants may lead to serious infection and secondary malignant tumours, and the use of biological agents is also limited to a certain extent because of its high cost [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cell therapy has become an attractive therapeutic strategy for various types of diseases [17][18][19][20], and it has achieved certain curative effects in induction therapy in patients with SLE [13]. The purpose of this study was to evaluate the efficacy of MSCs in the treatment of SLE by meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Since the standard immunosuppressive treatment is mostly insufficient in patients with severe proliferative lupus nephritis [93], the cell-based therapies are a promising alternative owing to their immunomodulatory properties. To date, many pre-clinical studies regarding the use of MSC transplantation in the context of lupus nephritis therapy have been performed giving mostly positive outcomes in terms of proteinuria and renal histopathology, as reviewed lately [94]. In one of the most recent experimental studies, Tani et al applied systemic treatment with low-dose allogenic bone marrow MSC (10 6 cells/kg body weight intravenously) in a mouse model of spontaneously developing lupus with co-occurring glomerulonephritis.…”
Section: Research On the Use Of Mesenchymal Stem Cells In Kidney Dmentioning
confidence: 99%
“…An analysis of LN patients even showed that there had not been a major improvement in outcome in the last 30 years to 2011 [10], indicating that the conventional drugs are unlikely to produce any further clinically important improvements. Aside from the poor efficacy, long-term usage of nonspecific immunosuppressive regimens may increase the risk of serious infection and secondary malignant tumors; besides, because of its high cost, the use of biological agents is also limited [11, 12]. Thus, there is an urgent need for safer and more effective treatments for LN.…”
Section: Introductionmentioning
confidence: 99%